2009
DOI: 10.5194/acp-9-1805-2009
|View full text |Cite
|
Sign up to set email alerts
|

Air-sea fluxes of biogenic bromine from the tropical and North Atlantic Ocean

Abstract: Abstract. Air-sea fluxes and bulk seawater and atmospheric concentrations of bromoform (CHBr 3 ) and dibromomethane (CH 2 Br 2 ) were measured during two research cruises in the northeast Atlantic (53-59 • N, June-July 2006) and tropical eastern Atlantic Ocean including over the African coastal upwelling system (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) • N May-June 2007). Saturations and sea-air fluxes of these compounds generally decreased in the order coastal > upwellin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
133
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(152 citation statements)
references
References 40 publications
12
133
7
Order By: Relevance
“…While do not identify a specific local cause of these high mixing ratios, previous studies have typically found such levels of CHBr 3 when seaweed are nearby (e.g. Carpenter and Liss, 2000;Pyle et al, 2011). Aside from these periods, mixing ratios at Tawau are usually within the range 1-2 ppt.…”
Section: J Ashfold Et Al: Estimates Of Tropical Bromoform Emissimentioning
confidence: 99%
See 2 more Smart Citations
“…While do not identify a specific local cause of these high mixing ratios, previous studies have typically found such levels of CHBr 3 when seaweed are nearby (e.g. Carpenter and Liss, 2000;Pyle et al, 2011). Aside from these periods, mixing ratios at Tawau are usually within the range 1-2 ppt.…”
Section: J Ashfold Et Al: Estimates Of Tropical Bromoform Emissimentioning
confidence: 99%
“…To do this we briefly discuss two variables, ocean depth and surface chlorophyll a concentration, that have been related to CHBr 3 emissions in previous studies (e.g. Carpenter et al, 2009;Palmer and Reason, 2009;Ordóñez et al, 2012). Figure 9 shows PDFs for surface elevation (negative values give ocean depth) and chlorophyll a concentration for the whole of the tropics and for the "fine" grid cells.…”
Section: Extrapolated Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current emissions estimates for these climaterelevant compounds remain fairly uncertain owing to the large spatial and temporal variability in observed halocarbon mixing ratios and fluxes. This is, in particular, true for short-lived halocarbons such as iodomethane (CH 3 I) and bromoform (tribromomethane, CHBr 3 ), [8][9][10][11][12][13][14] with the largest uncertainties in the known sources being observed for coastal and near-shore emissions. [15] Despite the uncertainties in global halocarbon emission budgets, it is well accepted that in the marine realm, diverse autotrophic organisms contribute to halocarbon production.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the biogeochemical controls of the production-destruction equilibrium may substantially improve current emission estimates [10,12] and is of vital importance to address potential future changes. Carbon isotope signatures of individual halocarbons have been proposed as a valuable tool to distinguish between different sources, to obtain information on source and sink mechanisms and to refine the global budgets of CH 3 Br [35] and CH 3 Cl.…”
Section: Introductionmentioning
confidence: 99%